2015
DOI: 10.1118/1.4908224
|View full text |Cite
|
Sign up to set email alerts
|

Optimization approaches to volumetric modulated arc therapy planning

Abstract: Volumetric modulated arc therapy (VMAT) has found widespread clinical application in recent years. A large number of treatment planning studies have evaluated the potential for VMAT for different disease sites based on the currently available commercial implementations of VMAT planning. In contrast, literature on the underlying mathematical optimization methods used in treatment planning is scarce. VMAT planning represents a challenging large scale optimization problem. In contrast to fluence map optimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(115 citation statements)
references
References 63 publications
3
109
0
3
Order By: Relevance
“…One advantage of sliding window VMAT is the technique’s capability to faithfully reproduce optimized fluence maps. Leaf traversal across the entire width of the target for each arc sector can, however, be time consuming, which makes the sliding window technique a relatively time‐consuming form of delivery . We have shown that the delivery time for sliding window VMAT can be considerably reduced if the collimator angle is chosen with care.…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of sliding window VMAT is the technique’s capability to faithfully reproduce optimized fluence maps. Leaf traversal across the entire width of the target for each arc sector can, however, be time consuming, which makes the sliding window technique a relatively time‐consuming form of delivery . We have shown that the delivery time for sliding window VMAT can be considerably reduced if the collimator angle is chosen with care.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a potential to improve the dosimetric quality of a treatment plan by utilizing an additional photon energy beam as an extra degree of freedom through simultaneous optimization process. To our knowledge, this notion has not been reported in any of the previous literatures for VMAT treatment planning.…”
Section: Introductionmentioning
confidence: 70%
“…We consider IMRT plans consisting of 19 equispaced coplanar beams, which approximates the best coplanar rotation therapy plan, which could be delivered with tomotherapy or VMAT [17]. We use a beamlet resolution of 5×5 mm.…”
Section: Methodsmentioning
confidence: 99%